Effects of Increasing Copper from Tri-basic Copper Chloride or a Copper-Chelate on Growth Performance of Nursery Pigs - C. Carpenter; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. L. Usry (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,452 pigs [Group 1; 350 barrows (DNA 200 × 400; initially 13.2 lb)] and [Group 2; 1,102 barrows and gilts (PIC 1050 × 280; initially 13.3 lb)] were used to determine the effects of added Cu source and level on nursery pig performance. There were 5 pigs per pen and 10 replications per treatment in group 1, and 24 to 27 pigs per pen and 6 replications per treatment in group 2. Pens of pigs were allotted by BW to 1 of 7 dietary treatments arranged as a 2 × 3 factorial plus a control diet, with main effects of Cu source: IntelliBond-C (TBCC; Micronutrients, Indianapolis, IN), or Mintrex-Cu (Cu-chelate; Novus, St. Charles, MO) and Cu level (50, 100, or 150 ppm). Diets were corn-soybean meal-based and were fed in meal form in 2 phases (d 0 to 14 and 14 to 35). All diets contained a trace mineral premix formulated to contribute 17 ppm of Cu from CuSO4to the complete diet. Overall (d 0 to 35), a Cu source × level interaction was observed (linear, P = 0.042) for ADG where the rate of improvement with increasing Cu was greater in pigs fed Cuchelate diets compared to those fed TBCC diets. Increasing added Cu increased (linear, P = 0.001) ADG, ADFI, and improved F/G. Although Cu source did not influence F/G, pigs fed Cu from Cu-chelate had greater (P ≤ 0.007) ADG and ADFI than those fed Cu from TBCC. In summary, these results suggest that increasing TBCC or Cuchelate can improve growth performance of nursery pigs and it appears that pigs provided Cu from Cu-chelate have greater ADG, ADFI, and d 35 BW, than those provided Cu from TBCC.
Keywords: nursery pig; copper; copper chelate; tri-basic copper chloride